Current Status Of Dental Plaque - ITISHA SINGH,; P.C.JAIN, (International Journal of Pharma and Bio Sciences, 2012)
The review deals with global position of the dental Streptococci are the initial colonizers in development of the dental plaque. They attach to the acquired pellicle on tooth surface and later on they show receptors for bonding with the secondary colonizers and late colonizersconditions leading to the development of dental Role of oral Streptococci in development of dental plaque/ biofilm formation is explained in depth. Quorum sensing (QS) in plaque forming bacteria is considered as one of the factors responsible for maintaining the plaque structure. Therefore quorum sensing in biofilm and regulation of gene expression in dental plaque is considered as one of the important factors. Use of antibiotics with special reference to antimicrobial resistance in plaque bacteria in dentistry is suggested because the structure of a biofilm may restrict the penetration of the antimicrobial agent as the bacteria growing on a surface display a novel phenotype, which can result in a reduced sensitivity to inhibitors.